(untitled) (Analysis in Theory and Applications, 2018)
We define Bloch-type functions of C^1(D) on the unit disk of complex plane C and characterize them in terms of weighted Lipschitz functions. We also discuss the boundedness of a composition operator C_φ00a0acting between two Bloch-type spaces. These obtained results generalize the corresponding known ones to the setting of C^1(D).